2018
DOI: 10.1007/s10551-018-3930-2
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Ethical Nudges: Does Inducing Hypocrisy Help or Hinder the Adoption of Pro-environmental Behaviors?

Abstract: To promote ethical and pro-environmental behavior, hypocrisy sometimes is made salient to individuals: i.e., they are made aware that their past behavior does not conform to expressed norms. The fact that this strategy may backfire and may even reduce the likelihood of individuals performing the desired action has been largely overlooked. This paper develops a theory of how hypocrisy stimulates two opposing heuristic processes: one that favors the former, positive outcome (the eco-citizenship effect) and one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 82 publications
(121 reference statements)
1
29
0
Order By: Relevance
“…This could be explained by research that has shown how increased salience of hypocrisy can also evoke a 'rebound' effect, where individuals harden their stance and refuse to change their habits. One reason for this might be that people find it easier to renege on their recent advocacy statement and change their beliefs to be in accordance with the transgression of the target behaviour, and find this a suitable way to relieve themselves from any negative affect arising from the arousal of dissonance [30,40,67,68]. We must understand the conditions of this rebound effect as it is important to understand when activating the salience of hypocrisy is useful or not [69].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be explained by research that has shown how increased salience of hypocrisy can also evoke a 'rebound' effect, where individuals harden their stance and refuse to change their habits. One reason for this might be that people find it easier to renege on their recent advocacy statement and change their beliefs to be in accordance with the transgression of the target behaviour, and find this a suitable way to relieve themselves from any negative affect arising from the arousal of dissonance [30,40,67,68]. We must understand the conditions of this rebound effect as it is important to understand when activating the salience of hypocrisy is useful or not [69].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has utilized a hypocrisy paradigm in order to induce hypocrisy in participants, resulting in increased uptake of pro-environmental, ethical, and pro-social behaviours [30][31][32][33][34][35]. The hypocrisy paradigm was pioneered by Aronson, Fried and Stone [36] who designed an experiment that has since reliably induced hypocrisy and dissonance.…”
Section: Hypocrisymentioning
confidence: 99%
See 3 more Smart Citations